Annual Plan 1970-71 Chandigarh Union Territory of Chandigarh - Planning Commission (Planning Commission, 1970)
As a consequence of the re-organisation of Punjab on the 1st November,1966, about 52 villages of Kharar Tehsil of erstwhile Ambala District constituted Union Territory of Chandigarh. the lands of about 24 villages had already been acquired for the development of first phase of Chandigarh Capital for a population of 1.5 lakhs. This area had been divided into 29 sectors (1 to 30 excluding number 13) of which 23 are residential while 6 are institutional/commercial sectors. An Industrial Area had also been created to the south eastern extremity of the town. the development of first phase had almost been completed up to the end of the Third Plan Period.
Union Territory of Chandigarh